Formation of occupied and unoccupied hybrid bands at interfaces between metals and organic donors/acceptors - Gerbert, David; Hofmann, Oliver; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2018)
Efficient charge transport in organic semiconductors and at their interfaces with electrodes is crucial for the performance of organic molecule-based electronic devices. Band formation fosters effective transport properties and can be found in organic single crystals of large π-stacking aromatic molecules. However, at molecule/metal interfaces, hybrid band formation and band dispersion is a rarely observed phenomenon. Using angle-resolved two-photon photoemission supported by density functional theory calculations, we demonstrate such band formation for two different molecule/metal systems, namely tetrathiafulvalene/Au(111) and tetrafluoro-tetracyanoquinodimethane/Au(111), in the energy region of occupied as well as unoccupied electronic states. In both cases, strong adsorbate/substrate interactions result in the formation of interface states because of hybridization between localized molecular states and delocalized metal bands. These interface states exhibit significant dispersions. Our study reveals that hybridization in combination with an extended well-ordered adsorption structure of the π-conjugated organic molecules is a striking concept to receive and experimentally observe band formation at molecule/metal interfaces.